On Civil Religion: New Horizon of Historical Explanations and Practical Development of Confucianism - CHEN, Ming (Journal of Research for Christianity in China (JRCC), 2025)
Civil religion in contemporary China relates to two issues: one is the religion of Confucianism and the other is the theory of state-building and nation-building. Since a sound theoretical basis for the relationship between Confucianism and civil religion would only be grounded on a careful consideration on the issue of state-building and nation-building, the latter theory seems to be more fundamental. From the imperial period to the party-sate regime, China inherits vast territory that had been conquered by the Qing dynasty since the seventeenth century. In order to establish a modern republic state, China, the multiethnic state, has to face practical problems and keep balance between two goals, i.e. realizing the modern value and rejuvenating the traditional Chinese culture. Both goals are keys and features of the state-building and nation-building in nowadays China; and the point of this dissertation, taking Confucianism as civil religion, also bases on such practical and historical considerations. It is the self-expectation and historical mission for Confucian intellectuals to actively participate into the course of civil religion building; meanwhile, it is also an internal requirement for Confucianism to be self-reflected and renovated profoundly.